THE EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL TO MATHEMATICAL COMMUNICATION SKILLS AND PROBLEM SOLVING 7 TH GRADE STUDENTS OF JUNIOR HIGH SCHOOL IN MERGANGSAN DISTRICTS OF YOGYAKARTA - Tiar Ayu Kuntari; Rosnawati Rosnawati (Universitas Negeri Yogyakarta, 2016)
AbstractThis study aims to determine the effect of problem based learning models for mathematicalcommunication and problem solving skills in grade VII students of Junior High School in districtMergangsan. The method in this study is a quasi experimental research with pre-test post-test groupdesign. The samples in this study are the students of Junior High School Taman Dewasa IbuPawiyatan of grade VIIA and VIIB, each of which is treated with problem-based learning andexpository model respctively. The instrument used in this study were the test and observation sheets.Data analysis technique used were T2-Hotteling test to determine the significance differences andfurther tests using independent sample t-test test. The results of statistics descriptive test analysisshowed that the problem based learning models give posttest average value higher than theexpository, namely for the class with problem-based learning models have the posttest averaged valueof 84.25 for mathematical communication skills and problem solving skills of 85.05,. While in theclassroom with expository have posttest average value of 71.64 and problem solving skills of 69.34.Based on the average results the model of problem-based learning is more influential and significantthan the expository teaching of the mathematical communication skills and problem solving.Keywords: Problem Based Learning, mathematical communication, problem solving.